2014
DOI: 10.1021/cm4041665
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Low-Field Magnetoresistance in La0.71Sr0.29MnO3 Nanoparticles Synthesized by the Nonaqueous Sol–Gel Route

Abstract: In colossal magnetoresistive (CMR) materials, magnetic fields of several tesla are typically required to exhibit large changes in electrical resistance, and hence, materials should be engineered to provide a more sensitive MR response at lower fields for their viability in practical applications. Enhanced low-field magnetoresistance (LFMR) was observed in highly ferromagnetic ∼20 nm La 0.71 Sr 0.29 MnO 3 particles synthesized by the nonaqueous sol−gel route. The enhanced LFMR of the nanoparticles (NPs) reaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 55 publications
(127 reference statements)
1
73
0
Order By: Relevance
“…By lowering the temperature, AFM ordering is increased significantly, and the core regime becomes broader, resulting in the less value in MR. Recently, similar kind of MR characteristics has been observed by Evetts et al 33 and Sadhu et al 34 Low field magnetoresistance (LFMR) behavior for PSMO 1150 and PSMO 850 samples are shown in the inset of Figs. 6(c) and 6(d), respectively.…”
Section: Magnetoresistance Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…By lowering the temperature, AFM ordering is increased significantly, and the core regime becomes broader, resulting in the less value in MR. Recently, similar kind of MR characteristics has been observed by Evetts et al 33 and Sadhu et al 34 Low field magnetoresistance (LFMR) behavior for PSMO 1150 and PSMO 850 samples are shown in the inset of Figs. 6(c) and 6(d), respectively.…”
Section: Magnetoresistance Propertiessupporting
confidence: 82%
“…It is reported that MR in manganite can be controlled by many factors especially spin disorder, non-collinear spin. 33,34,39 Finite magneto-resistance for all samples signify notable drop down in resistivity with an increase of applied field and promotes FM ordering in the compound by suppression of AFM ordered state. 40,41 In polycrystalline manganite, magneto-resistive property strongly depends on intrinsic part (MR INT ) (originates through DE interaction between two neighboring Mn ions), and intergranular spin-polarized tunneling (MR SPT ).…”
Section: Magnetoresistance Propertiesmentioning
confidence: 91%
“…[ 26 ] It is notable that the spin pinned effect occurs at the nanosized grain surface defect sites or spin coupling at the boundaries. [ 26,27 ] In addition, the short range ferromagnetic (FM) coupling order may add the opportunity of spin scattering even near the Curie temperature. [ 28,29 ] Thus it is speculated that the high-temperature LFMR in LSMO composite fi lms can be got through tuning the grain size and the FM coupling at the phase boundary.…”
mentioning
confidence: 99%
“…8 2 ) were taken in stoichiometric proportion and were dissolved in deionized water with subsequent addition of Citric acid and Ethylene Glycol. Afterwards, the monohydrate Citric acid and the Ethylene Glycol were added to ensure the homogeneity and the transparency of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…or monovalent alkaline metal ion, Na, Ag, K,…), have spurred considerable scientific and technological interest in recent decades due to their remarkable magnetic, electric transport, catalytic and colossal magnetoresistance (CMR) properties, etc. [1][2][3].…”
Section: Introductionmentioning
confidence: 99%